PENGARUH PENGGUNAAN MEDIA FLIPCHART BANGUN DATAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV DI SD MUHAMMADIYAH 1 BONTOALA MAKASSAR - Sandy, Mutiara; Ernawati; Rahma Tahir, Sitti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effect of using flipchart media on students’ mathematics learning outcomes in the topic of plane geometry for fourth-grade students at SD Muhammadiyah 1 Bontoala Makassar. The research employed a quantitative approach with an experimental method using a One Group Pretest–Posttest design. The sample consisted of 24 students selected through total sampling. Data were collected through pretest and posttest assessments, supported by observation sheets and student response questionnaires. The data were analyzed using descriptive and inferential statistics, including normality testing and a paired sample t-test with the assistance of SPSS software. The results revealed a significant increase in the mean score from 17.47 in the pretest to 83.30 in the posttest. The N-Gain value of 0.80 was categorized as high. Classical learning mastery improved from 0% to 87.50%. The hypothesis testing showed a significance value of 0.001 (p < 0.05), indicating a significant difference between students’ learning outcomes before and after the treatment. In addition, learning activities were categorized as very good, and students’ responses toward the use of flipchart media were highly positive. Therefore, flipchart media proved to be effective in improving elementary students’ mathematics learning outcomes.